A combined transcriptome - miRNAome approach revealed that a kinesin gene is differentially targeted by a novel miRNA in an apomictic genotype of Eragrostis curvula - Pasten, María Cielo; Carballo, José; Gallardo, Jimena; Zappacosta, Diego; Selva, Juan Pablo; Rodrigo, Juan Manuel; Echenique, Viviana; Garbus, Ingrid (Frontiers in Plant Science, 2022)
Weeping lovegrass (Eragrostis curvula [Shrad.] Nees) is a perennial grass typically established in semi-arid regions, with good adaptability to dry conditions and sandy soils. This polymorphic complex includes both sexual and apomictic cytotypes, with different ploidy levels (2x-8x). Diploids are known to be sexual, while most polyploids are facultative apomicts, and full apomicts have also been reported. Plant breeding studies throughout the years have focused on achieving the introgression of apomixis into species of agricultural relevance, but, given the complexity of the trait, a deeper understanding of the molecular basis of regulatory mechanisms of apomixis is still required. Apomixis is thought to be associated with silencing or disruption of the sexual pathway, and studies have shown it is influenced by epigenetic mechanisms. In a previous study, we explored the role of miRNA-mRNA interactions using two contrasting E. curvula phenotypes. Here, the sexual OTA-S, the facultative Don Walter and the obligate apomictic Tanganyika cDNA and sRNA libraries were inquired, searching for miRNA discovery and miRNA expression regulation of genes related to the reproductive mode. This allowed for the characterization of seven miRNAs and the validation of their miRNA-target interactions. Interestingly, a kinesin gene was found to be repressed in the apomictic cultivar Tanganyika, targeted by a novel miRNA that was found to be overexpressed in this genotype, suggestive of an involvement in the reproductive mode expression. Our work provided additional evidence of the contribution of the epigenetic regulation of the apomictic pathway.